Measurement of the aerothermodynamic state in a high enthalpy plasma wind-tunnel flow - Hermann, T; Loehle, S; Zander, F; Fasoulas, S (Elsevier, 2017)
This paper presents spatially resolved measurements of absolute particle densities of N2, N2+, N, O, N+, O+, e− and excitation temperatures of electronic, rotational and vibrational modes of an air plasma free stream. All results are based on optical emission spectroscopy data. The measured parameters are combined to determine the local mass–specific enthalpy of the free stream. The analysis of the radiative transport, relative and absolute intensities, and spectral shape is used to determine various thermochemical parameters. The model uncertainty of each analysis method is assessed. The plasma flow is shown to be close to equilibrium. The strongest deviations from equilibrium occur for N, N+ and N2+ number densities in the free stream. Additional measurements of the local mass-specific enthalpy are conducted using a mass injection probe as well as a heat flux and total pressure probe. The agreement between all methods of enthalpy determination is good.